Assessing wind energy development in Uganda: Opportunities and challenges - Wabukala, Benard M; Otim, Jacob; Mubiinzi, Geoffrey; Adaramola, Muyiwa S (SAGE Publications, 2021)
In this paper, we utilize a systematic review to assess opportunities and challenges in wind energy development in Uganda. Apart from being an environmentally friendly and renewable energy resource, development of wind energy could boosts economic growth and creates jobs. For Uganda, rising energy demand, need to reduce greenhouse gas emissions, and increasing electricity access to rural areas, emerge as rational opportunities to invest in wind energy. The main obstacles to wind energy development in Uganda are insufficient wind resource data, high initial investment cost, inadequate research and development, weak infrastructure, and unsupportive policies. For policy, comprehensive wind resource assessment, energy infrastructure investment, financial de-risking, capacity building, and deliberate wind power policy incentives could accelerate wind energy development and consequently contribute to the country’s energy security.
Keywords: Energy security, increasing energy demand, rural electrification, energy policy, employment creation